Maintaining Quality of Life: Electrochemotherapy for Palliative Periorbital Malignancy. Issue 6 (November 2019) - Ullrich, Katja; Bisase, Brian; Kumar, Siva; Malhotra, Raman
Abstract : Electrochemotherapy has been used successfully for treatment of recurrent head and neck skin cancers and skin metastasis. It combines both electroporation and chemotherapy. The authors report 4 patients, who all had metastatic periorbital malignancy. These patients were palliative with widespread metastatic malignancy. All patients had either already had multiple procedures or declined surgical resection and preferred less involved measures. The authors report technique and outcomes. Patient 1: 83-year-old man with recurrent malignant melanoma (MM) nodules (BRAF negative) in the left medial orbit and medial canthal area after rhinectomy and previous resections. Patient 2: 72-year-old man with metastatic MM who developed painful and unsightly metastatic nodules on the right and left forehead and the left medial canthus. Patient 3: 93-year-old man with background of widespread multiple myeloma, considered palliative. He developed a left forehead SCC, apparent as a fungating ulcer, which caused significant pain due to perineural invasion. Patient 4: 91-year-old woman with recurrent metastatic sebaceous cell carcinoma of the left lower eyelid obstructing her vision. All patients experienced an improvement in their pain and quality of life. None of the patients developed any significant periorbital inflammation or adverse complications. Electrochemotherapy may be a useful palliative treatment for periorbital tumors. It improves pain and reduces tumor volume. It can be considered for tumors where palliative radiotherapy may be contraindicated. Electrochemotherapy is a useful palliative treatment for metastases to the periorbital area, improving pain and size of the tumors.